Isolation and characterization of Escherichia coli mutants defective for phenylpropionate degradation. - Burlingame, R P (1986)
Mutants of Escherichia coli defective in catabolism of 3-phenylpropionate, 3-(3-hydroxyphenyl)propionate, or both were isolated after mutagenesis with ethylmethane sulfonate. Nine phenotypically distinct classes of mutants were identified, including strains lacking each of the first five enzyme activities for the degradation of these compounds and mutants pleiotropically negative for some of these activities. Characterization of these mutants was greatly facilitated by the use of indicator media in which accumulation of 3-(2,3-dihydroxyphenyl)propionate or 2-hydroxy-6-ketononadienedioic acid led to the formation of dark red or bright yellow colors, respectively, in the medium. Assays with wild-type and mutant strains indicated that 3-phenylpropionate (or its dihydrodiol), but none of the hydroxylated derivatives tested, induced the synthesis of enzymes for its conversion to 3-(2,3-dihydroxyphenyl)propionate. The remaining enzymes were induced by the 2- or 3-hydroxy or 2,3-dihydroxy derivatives of 3-phenylpropionate, with the 2-hydroxy compound acting as an apparent gratuitous inducer. Metabolism to nonaromatic intermediates appeared to be unnecessary for full induction of any pathway enzyme. One unusual class of mutants, in which 2-keto-4-pentenoate hydratase appeared to be uninducible, indicated a level of control not previously shown in meta-fission catabolic pathways.